TINGKAT MOTIVASI BELAJAR PENCAK SILAT (STUDI EMPIRIS PADA SISWA EKSTRAKURIKULER PENCAK SILAT TAPAK SUCI SMP AHMAD DAHLAN KABUPATEN SUKOHARJO) - Mustaqim, Wahyu Nur; Gatot Jariono; Eko Sudarmanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to identify the level of student learning motivation in the Tapak Suci pencak silat extracurricular activity at SMP Ahmad Dahlan, Sukoharjo Regency. The purpose of this study was to determine the Pencak Silat Learning Motivation of Students in the Tapak Suci Pencak Silat Extracurricular at SMP Ahmad Dahlan, Sukoharjo Regency. This study is a quantitative descriptive study, with a survey method. Data collection techniques using questionnaires. The results obtained were the level of student learning motivation for internal factors obtained an average score of 80.87% while external learning motivation was 73.06%. So that the level of student learning motivation in participating in the Tapak Suci pencak silat extracurricular activity is generally high, with an average percentage of 76.96% so that most students have a strong drive to be actively involved in pencak silat training.